Phytoremediation of Wastewater with Walnut Shells as Substrate (Journal of Engineering, 2026)
Phytoremediation is considered an attractive and green method of treating urban wastewater, especially in developing countries, due to its low operating cost and sustainable environmental option. This research aimed to evaluate an advanced method of phytoremediation using natural media composed of walnut shells and gravel with peace lily plants (S. Cochlearispathum) for treating real wastewater with methyl orange dye. A Lab-scale of three tanks, the first one is wastewater only as a control containment (WW), the second tank includes substrate only (WS), and the third one includes substrate with the plant of S. Cochlearispathum (WSP). The experiment was operated with a batch system. The WSP tank recorded the highest treatment efficiency, where the percentage removal was found to be 61.60% for TSS, 65.70% for color, 82.35% for nitrate, and 67.90% for phosphate. Overall, walnut shells as a substrate with phytoremediation were found to significantly improve the treatment of wastewater, which can be a feasible, economical, and sustainable technique for developing regions.